Mapa do sobrepeso e da obesidade em escolares da cidade de Curitiba, Paraná - Silveira, Marcia Cristina da (2019)
Introduction: In recent decades, a profound change has been taking place in the habits and customs of the population, with the nutritional profile being one of the most impacted. Malnutrition decreased and reached levels acceptable by the WHO. On the other hand, there was a vertiginous growth in the increase in the prevalence of overweight and obesity, resulting in a worsening in nutritional status. In Brazil, there was an inversion in the picture presented, from malnutrition to obesity in years before. Objectives: Create a database of schoolchildren, describe their nutritional status and draw up a map of overweight and obesity in the city of Curitiba, Paraná. Methods: The study was carried out with 9,360 students from public and private schools, aged between 6 and 17 years. The databases were provided by researchers from the Center for the Study of Physical Activity and Health (CEAFS) and the Study and Research Group on Physical Activity, Sport and Technology (GEPAFETec), the collections were carried out between 2010 and 2018. The methodology used was descriptive, crosssectional through an epidemiological survey, which made it possible to carry out the secondary exploration of databases. Indicators of body mass, BMI, height, sex and age were used to diagnose the nutritional status of schoolchildren, according to the WHO criteria. Data were tabulated in an Excel spreadsheet and entered into the Tableau Prep Builder software, analyzed using the IBM SPSS® version 20.0 software. The maps were generated in Tableau Desktop software. Student’s t-test was performed for independent samples and the asymmetric distribution values were presented as medians. The association between overweight, obesity and other variables was investigated using the Pearson chi-square test. For all statistical treatments, p≤0.05 was assumed as a significant value. Results: The nutritional status of students showed the following results: 10.26% of males were underweight, and 8.50% of females. For normal weight, this percentage was 56.79% for males and 60.47% for females. The values found for overweight were 19.46% for boys and 19.98% for girls. The obesity rate was 13.49% and 11.05%, respectively. When adding the overweight and obesity indices (SP + OB), males have 32.95% and females 31.03%. Conclusion: It is concluded that there is a prevalence of normality in most students, but the cases of overweight and obesity are quite high, that is, 33% of the analyzed sample. It can also be observed that the prevalence rate of overweight and obese together is three times higher when compared to underweight.